2019
DOI: 10.1590/0366-6913201965s12604
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical properties of porous alumina ceramics obtained using rice husk as a porogenic agent

Abstract: The objective of this work was to evaluate the mechanical properties of porous alumina ceramics, using the rice husk as a porogenic element. The rice husk was milled and graded in two granulometry, <65 μm and 65-150 μm, and added in a high purity calcined alumina in the proportion of 5, 15 and 30 wt%. The samples were pressed by uniaxial pressing and sintered at 1450 ºC for 1 h. Sintered density, total porosity, Young's modulus, modulus of rupture, and compressive strength were evaluated. Samples were also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The pore structures contain tiny and big pores and can prevent the content of the polymer powders to recognize the accurate control of the permeability of the final product. The schematic representation of the pore-forming agent method for porous ceramic production (Ribeiro et al 2019) is shown in Fig. 4.…”
Section: Powdersmentioning
confidence: 99%
“…The pore structures contain tiny and big pores and can prevent the content of the polymer powders to recognize the accurate control of the permeability of the final product. The schematic representation of the pore-forming agent method for porous ceramic production (Ribeiro et al 2019) is shown in Fig. 4.…”
Section: Powdersmentioning
confidence: 99%
“…where: m RH : initial mass of rice husk; and m SiO2 : final mass of silicon dioxide obtained from rice husk. Thus, following the present methodology, 100 g of in natura rice husks generate around 20 g of resulting material, which is associated with a high content of silicon dioxide [4,6,20]. Despite its low market value, it is acceptable due to the rice husk be an abundant waste in the South Region of Brazil [26].…”
Section: Resultsmentioning
confidence: 96%
“…The silicon dioxide can be obtained from rice husk by thermal treating, which can be enhanced by a previous acid/alkaline leaching process [5]. Due to the high content of silicon dioxide found on in natura rice husk [6], the resulting material has silicon dioxide content varying between 96% to 99% [7], strongly dependent on chosen processes, e.g., the parameters used in the leaching process (acid/base concentration, mixing time,…”
Section: Introductionmentioning
confidence: 99%
“…The 40 wt.% starch sample doped with niobium retained a maximum porosity of 57% and a compressive strength of 60 MPa. Ribeiro et al [22] used the rice husk as a pore-forming agent to prepare porous alumina ceramic membranes with a total porosity ranging from 24% to 54%. In Ref.…”
Section: Introductionmentioning
confidence: 99%